The zeros of a quadratic function are the points where the graph cuts the x axis.
If one zero is - 3, it means that
x = - 3
x + 3 = 0
Thus, one of the factors is (x + 3)
If another zero is - 13, it means that
x = - 13
x + 13 = 0
Thus, one of the factors is (x + 13)
Thus, the quadratic function would be
(x + 3)(x + 13)
We would open the brackets by multiplyingeach term inside one bracket by each term inside the other. Thus, we have
x * x + x * 13 + 3 * x + 3 * 13
x^2 + 13x + 3x + 39
x^2 + 16x + 39
Thus, the quadratic function is
f(x) = x^2 + 16x + 39